2018
DOI: 10.1177/1359105318763494
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating the health literacy skills of parents: A photovoice study

Abstract: Parents play a vital role in promoting children's health. The parental health literacy skills are important since the decisions they make can have an impact on other family members' health and well-being. Using an assets-based approach, this project aimed to explore the skills parents use to communicate health messages with their children and how they manage their family's health. Six adult parents of children aged 0-16 years old took part in this photovoice study. The thematic analysis suggests that tapping i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Since then, the use of qualitative research methods has become more common as researchers have started to recognise how studying the perspectives of patients rather than healthcare professionals provides insight into constructs that either might not be included on the health literacy tests that continue to dominate the field, or might be hard to measure (Jordan et al, 2010). However, there have still been relatively few attempts to examine the affordances of arts-based methods within health literacy research, including the role that these methods can play in continuing to challenge dominant deficit discourses (e.g., Estacio et al, 2020;Gahagan & Colpitts, 2017;Lupton, 2019). Future research could continue to build on this work, as well as drawing from sociocultural information literacy studies that have explored how visual research methods can provide insight into tacit and nuanced forms of knowing (Eckerdal, 2011;Hicks & Lloyd, 2018) to extend understanding…”
mentioning
confidence: 99%
“…Since then, the use of qualitative research methods has become more common as researchers have started to recognise how studying the perspectives of patients rather than healthcare professionals provides insight into constructs that either might not be included on the health literacy tests that continue to dominate the field, or might be hard to measure (Jordan et al, 2010). However, there have still been relatively few attempts to examine the affordances of arts-based methods within health literacy research, including the role that these methods can play in continuing to challenge dominant deficit discourses (e.g., Estacio et al, 2020;Gahagan & Colpitts, 2017;Lupton, 2019). Future research could continue to build on this work, as well as drawing from sociocultural information literacy studies that have explored how visual research methods can provide insight into tacit and nuanced forms of knowing (Eckerdal, 2011;Hicks & Lloyd, 2018) to extend understanding…”
mentioning
confidence: 99%
“…Regardless of parental health literacy levels, parents prefer to use technology for health provider's communication (Meyers et al, 2020). Parent's social skills such as the establishment of pleasant relationships with the healthcare provider and communication strategies such as gamifying health messages and encouraging children to be independent have been successful in promoting healthy behaviours in children (Estacio et al, 2020). Merlino et al (2020) have shown that external support structures consisting of family and friends play an integral role in imparting health literacy to young people, particularly indigenous males.…”
Section: Health Literacymentioning
confidence: 99%
“…, 2020). Parent's social skills such as the establishment of pleasant relationships with the healthcare provider and communication strategies such as gamifying health messages and encouraging children to be independent have been successful in promoting healthy behaviours in children (Estacio et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several negative health outcomes have been observed in children of parents with low health literacy, such as poor eating habits, increased risk of obesity, chronic kidney disease, diabetes, and oral health problems [11][12][13][14][15][16]. Therefore, the adoption of informed and knowledge-based approaches by parents can have a positive impact on the overall health of their children [17,18].…”
Section: Introductionmentioning
confidence: 99%